2012
DOI: 10.1111/j.1477-2574.2011.00401.x
|View full text |Cite
|
Sign up to set email alerts
|

Biliary complications after right lobe living donor liver transplantation: a single-centre experience

Abstract: Identification of more than one biliary orifice in the graft resulted in an increase in the complication rates. In grafts containing multiple orifices, performing multiple duct-to-duct (DD) or Roux-en-Y anastomoses led to a lower number of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 13 publications
3
18
0
2
Order By: Relevance
“…Living-donor and DCD grafts are at significantly higher risk for biliary complications. [36][37][38][39][40][41] In our series, the overall bile leak rate was 11.6% and the overall biliary stricture rate was 16.4%. When we evaluated the subgroups, the highest rates were observed in the adult LDLT group, with a bile leak rate 13.1% and a biliary stricture rate 23.6% (Table 4).…”
Section: Discussionmentioning
confidence: 47%
“…Living-donor and DCD grafts are at significantly higher risk for biliary complications. [36][37][38][39][40][41] In our series, the overall bile leak rate was 11.6% and the overall biliary stricture rate was 16.4%. When we evaluated the subgroups, the highest rates were observed in the adult LDLT group, with a bile leak rate 13.1% and a biliary stricture rate 23.6% (Table 4).…”
Section: Discussionmentioning
confidence: 47%
“…However, the studies about the clinical manifestations, complications, and mortality based on the type of donor reported many different results. Some studies reported similar biliary complications between LDLT and deceased donor liver transplantation (DDLT) (34). Quintini et al (5) found that LDLT is safe and, in select cases, offers advantages over DDLT.…”
Section: Introductionmentioning
confidence: 99%
“…So far, it remains unclear whether using a living donor (LD) graft with multiple BDs increases the risk for the development of postoperative anastomotic biliary complications or even graft loss. Although some groups reported an increased complication rate using LD grafts with multiple BDs, others did not find an association between the development of biliary strictures and the number of BDs …”
mentioning
confidence: 96%